2004
DOI: 10.1093/tropej/50.3.149
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immunoglobulin E in Idiopathic Nephrotic Syndrome

Abstract: Serum immunoglobulin E (IgE) and absolute eosinophil count (AEC) were assayed in 48 children with idiopathic nephrotic syndrome and 20 controls. The mean serum IgE (p < 0.001) and AEC (p < 0.05) were significantly raised in active nephrotic syndrome compared with controls. The mean values of IgE and AEC in nephrotic patients were 228.6 and 164.5 per cent of the normal mean, respectively. The serum IgE and AEC were significantly abnormal in all the subgroups (first attack, infrequent, and frequent relapsers), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 0 publications
4
15
0
1
Order By: Relevance
“…2,3 In many studies, increased incidence of allergic diseases and high serum IgE levels have been reported in SSNS. 2,[4][5][6]9,[16][17][18][19] These findings support the existence of a dysfunction of the humoral immune response in the nephrotic syndrome. 4,6,7,18,19 The term ''atopy'' is used to define IgE-mediated diseases.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…2,3 In many studies, increased incidence of allergic diseases and high serum IgE levels have been reported in SSNS. 2,[4][5][6]9,[16][17][18][19] These findings support the existence of a dysfunction of the humoral immune response in the nephrotic syndrome. 4,6,7,18,19 The term ''atopy'' is used to define IgE-mediated diseases.…”
Section: Discussionsupporting
confidence: 56%
“…2,[4][5][6]9,[16][17][18][19] These findings support the existence of a dysfunction of the humoral immune response in the nephrotic syndrome. 4,6,7,18,19 The term ''atopy'' is used to define IgE-mediated diseases. Atopic individuals are genetically sensitive toward widespread allergens and produce IgE antibodies; cytokines like IL-4 and IL-13 produced by T helper 2 (Th-2) cells.…”
Section: Discussionsupporting
confidence: 56%
“…In recent years, studies have reported that increased serum IgE concentrations in patients with NS were closely associated with NS and allergic disorders. [6][7][8]28,31 The synthesis of IgE is mainly mediated by two cytokines, interleukin (IL)-4 and IL-13, released by T-helper 2 (Th2) cells. 32 Increased concentrations of IL-4 and IL-13 have been reported in children with NS.…”
Section: Discussionmentioning
confidence: 99%
“…Most,13-15,18,22,25-28 but not all,17,29 studies have reported greater serum IgE levels in patients with MCD compared with controls. Not infrequently, increased IgE levels occur in the absence of other clinical findings of atopy 13,16.…”
Section: Atopymentioning
confidence: 97%